AN INVESTIGATION TO FIND OUT THE REASONS FOR ADOPTION OF AGROFORESTRY BY FARMERS IN DISTRICT FAISALABAD - W. Nouman; G. S. Khan; H. Farooq; N. Jamal (Journal of Animal and Plant Sciences, 2006)
Forests play an important role in Pakistan’s economy. These are the important sources for provision of timber, fuel wood, fodder and shelter for livestock. The significance of wood produced on farmlands has increased sharply during the last two decades. The cultivated fields are the best places to grow trees along with crops. The objective of this study was to investigate the reasons and the factors, which are responsible for the adoption of agroforestry by farmers in district Faisalabad. A sample of 125 respondents from five randomly selected rural union councils of tehsil Faisalabad were interviewed through a structured interview schedule in person and the data were analyzed by using computer software to draw conclusions. It was concluded that the farmers were adopting agroforestry practices mainly to meet their fodder and fuel wood requirements. They highly preferred Delibergia sissoo and Acacia nilotica for better economic returns.
Keywords: Agroforestry; Tree benefits; Sheltering crops.